Influence of Dopants, Temperature and Atmosphere of Sintered on the Microstructure and Behavior of Lead Free Ceramics - Zaghete, Maria A.; Moura, Francisco; Simões, Alexandre Z.; A.Varela, José; Longo, Elson (IntechOpen, 2011)
None